pH-controlled self-assembling of meso-tetrakis(4-sulfonatophenyl)porphyrin-chitosan complexes - Synytsya, Alla; Synytsya, Andriy; Blafková, Petra; Ederová, Jana; Spevacek, Jiri; Slepicka, Petr; Král, Vladimír; Volka, Karel (Biomacromolecules, 2009)
Solid meso-tetrakis(4-sulfonatophenyl)porphyrin (TPPS(4))-chitosan supramolecular complexes were prepared by addition of porphyrin to an aqueous solution of chitosan at pH values. The precipitates obtained were assigned as 1 (pH 6.8) and 2 (pH 2.5) and characterized by spectroscopic, thermal, and microscopic methods. Spectroscopic investigation confirmed the presence of TPPS(4) and chitosan in both products and that the porphyrin is highly self-associated. H-type (stacked) of TPPS(4) aggregation was proposed for 1 and J-type (tilted) for 2. Thermal analysis revealed different pyrolysis routes of the complexes depending on their structural diversity. Light microscopic analysis indicated fibrous and lamellar microstructures, respectively, for 1 and 2. SEM and AFM analysis showed that both complexes consist of compact nanostructures; their size and interconnection is different for 1 and 2. Based on structural inferences, self-assembling hierarchy models were proposed for both of the TPPS(4)-chitosan supramolecular complexes.
Keywords: nanostruktury; mikroskopie atomárních sil; velikost částic; Porphyrins; Hydrogen-Ion Concentration; teplota; porfyriny; Particle Size; Spectroscopy, Near-Infrared; povrchové vlastnosti; Molecular Structure; blízká infračervená spektroskopie; chitosan; Chitosan; Temperature; molekulární struktura; magnetická rezonanční spektroskopie; Microscopy, Atomic Force; Nanostructures; Magnetic Resonance Spectroscopy; koncentrace vodíkových iontů; Surface Properties